The effect of spraying alpha-tociferol and the amino acid Phenylalanine on the vegetative and floral growth of Mirabilis Jalapa L. - Hussein, Ali; Rasha Kazim , Rasha; Haider Subaih Shanu , Haider Subaih Shanu (University of Thi-Qar Journal of agricultural research, 2025)
The experiment was conducted in the fabric shade of the Department of Horticulture and Landscape Engineering - College of Agriculture - University of Basra, Karma Ali site, during the agricultural season 2023-2024. The seeds were planted on 10/15/2023 directly in two plastic anvils with a capacity of 5 kg per kilo, with three seeds in each anvil. After germination and the appearance of true leaves, the plants were thinned and only one plant remained. The experiment included studying the effect of two factors: spraying the amino acid Phenylalanine at four concentrations: comparison (spraying with distilled water) and spraying with the amino acid Phenylalanine at a concentration of 50 mg. L-1, 100 mg. L-1, and 150 mg. L-1, and spraying with Alpha-Tocopherol at four concentrations: comparison (spraying with distilled water), 50 mg. L-1, and 100 mg. L-1 and 150 mg L-1. The study showed that the plants sprayed with alpha-tocopherol and the amino acid Phenylalanine at a concentration of 150 mg L-1 were significantly superior to the other two concentrations in most of the studied traits, such as plant height (cm), number of leaves (leaf/plant-1), leaf area (cm2), number of branches (branch/plant-1), number of flowers (flower/plant-1), leaf content of total soluble carbohydrates (mg/100 gm-1 fresh weight), leaf content of mineral elements, percentage of nitrogen (%), percentage of potassium (%), percentage of phosphorus (%).